Atomically resolved electroluminescence from individual vacancy defects in molybdenum disulfide - Singh, Gagandeep (Nanyang Technological University, 2024)
Resolving light-matter interaction in crystalline solids at the nano-or even atomic scale can give unprecedented insight into fundamental quasiparticle excitations. Yet many optoelectronic processes occur at length scales far below the diffraction limit of light (≈ 100 nm) making them inaccessible to conventional optical spectroscopy at an individual level. Examples are atomically confined excitons, bound to atomic defects or color centers, as well as short-wavelength plasmonic processes in 2D semimetals such as graphene. Combining scanning tunnelling microscopy (STM) with optical spectroscopy can provide access to optoelectronic processes with the true atomic resolution. Here, we demonstrate a setup developed to collect light emission from a STM tunnel junction. We show that exciting individual sulfur vacancies in MoS2 with an atomically precise single-charge tunneling current from an STM tip gives rise to highly localized, to within 1 nm, electroluminescence with single-photon character and reflecting orbital structure of the defect’s wavefunction. The single photon character is reflected in a saturation in the photon emission rate as a function of excitation current and is well described by a two-state rate equation model. At high bias, each tunneling electron can yield more than one photon, as evidenced by super-bunching in photon correlation measurements. We believe that our results have relevance towards realizing electrically excited on-demand quantum emission using single atomic defects.